A review of routing protocols for child tracking in wireless sensor network - Rozyyev, Azat; Hasbullah, Halabi (2010)
One of the widespread types of crime is child kidnapping where the number of cases is increasing each year. With the modern telecommunication technology, the child protection should be better now than before. This paper presents a preliminary study on routing protocol for child tracking using combined infrastructure of Wireless Sensor Network and Cellular Network. The real-time application in these networks would help the related parties to track the location of the missing child. From proactive point of view, the application would act as a preventive tool for child kidnapping. When the sensors in a Wireless Sensor Network detect child’s presence, they have to transmit the data to an Access Point or the sink node in the network. Many routing protocols have been developed in the past, and all of them have their advantages and disadvantages. The outcome of this study is the selection of a routing protocol that is suitable for child tracking in Wireless Sensor Network.